Waste biomass as sources for activated carbon production-A review (Bangladesh Journal of Scientific and Industrial Research, 2013)
A review of the production of activated carbons from waste biomass has been presented. The effects of various process parameters on the pyrolysis stage have been reviewed. Influences of activating conditions, physical and chemical, on the active carbon properties have been discussed. Under certain process conditions several active carbons with BET surface areas, ranging between 250 and 2410 m2/g and pore volumes of 0.022 and 91.4 cm3/g, have been produced. A comparison in characteristics and uses of activated carbons from waste biomass with those of commercial carbons has been made. Waste biomass being highly efficient, low cost and renewable sources of activated carbon production. Bangladesh J. Sci. Ind. Res. 47(4), 347-364, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14064